متطلبات ومعوقات تطبيق إدارة المعرفة (جامعة تشرين نموذجاً) - غدير, باسم (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى تحديد متطلبات ومعوقات تطبيق إدارة المعرفة في جامعة تشرين. حيث تكوّن مجتمع الدراسة من العاملين في الإدارة المركزية في جامعة تشرين. استخدم الباحث الاستبانة كأداة لجمع البيانات من عينة ميسّرة، حيث تم توزيع (200) استبانة وتم استرداد (160). وقد توصّلت الدراسة إلى وجود متطلبات ملحّة لتطبيق إدارة المعرفة تتمثّل بالثقافة التنظيمية والهيكل التنظيمي وتكنولوجيا المعلومات, إضافة إلى وجود جملة من المعوقات المباشرة أهمها: عدم وضوح مفهوم إدارة المعرفة لدى معظم أفراد العينة المدروسة، وعدم تخصيص التمويل الكافي لتطبيقها في جامعة تشرين.This study aimed to determine the requirements and constraints of the application of knowledge management at Tishreen University. The study area was a set of employees in the central administration of Tishreen University. The researcher used the questionnaire as a tool to collect data, where 160 questionnaires were recovered from a total of 200 distributed. The result of this study found an urgent requirement for the application of knowledge management is the organizational culture, organizational structure and information technology, in addition to a number of direct obstacles, including: lack of clarity of the concept of knowledge management at most of the studied sample, and failure to allocate sufficient funding to be applied at Tishreen University.